PREPARAÇÃO, CARACTERIZAÇÃO E APLICAÇÃO DE FILMES LbL COM NANOPARTÍCULAS DE PRATA ESTABILIZADAS EM AMIDO - Oliveira, Rafaela Daiane de (2014)
In this work, starch-stabilized silver nanoparticles (AgNPs-Am) were synthesized by reduction of AgNO3 using the NaBH4. The temperature and concentration of reagents of the synthesis were optimized. The formation of AgNPs-Am was monitored by UV-Vis spectroscopy and dynamic light scattering (DLS). The optimum conditions found for the AgNPs-Am synthesis were starch 0.6 % (w/v), 3.6 x 10-3 mol L-1 NaBH4, 0.9 x 10-3 mol L-1 AgNO3 and synthesis in bath ice. The average size of the AgNPs-Am was between 21 and 77 nm. Transmission electron microscopy (TEM) confirmed the AgNPs-Am formation inside and outside of the starch chains, however the smaller sizes were referred to the NPs stabilized by starch. Measurements of Potential zeta indicated stability of the particles, confirmed by DLS monitoring that demonstrated low agglomeration of NPs in a period of 115 days. For the characterization of AgNPs-Am it was also used infrared spectroscopic (FTIR) and X-ray diffraction (XRD). The AgNPs-Am were applied as polyanion for the construction of films by Layer-by-Layer technique (LbL), alternating with polycation 3-n-propylpyridinium-silsesquioxane (SiPy+Cl-). In order to obtain the films, pH and immersion time of the polyelectrolytes were optimized, as well as the concentration of SiPy+Cl-, monitoring the deposition by UV-Vis. The optimum parameters were immersion time 240 seconds, 2 mg/mL SiPy+Cl- pH 6.5 and AgNPs-Am pH 9.0. Atomic force microscopy (AFM) images showed that film thickness increases linearly and the roughness decrease with the bilayers number. FTIR spectra and Raman confirmed the interaction between the polyelectrolytes in the assembly of LbL films. The LbL films with architecture (SiPy+Cl-/AgNPs-Am)n (n = bilayers number) were applied as modified electrodes for iodine detection, using differential pulse voltammetry (DPV). It was verified that interaction of the components in the LbL films improved the current intensity. The film (SiPy+Cl-/AgNPs-Am)n (n=5) showed better current response in phosphate buffered saline (PBS) 0.1 mol L-1 pH 7.0. The instrumental parameters Epulse, and tpulse were optimized by 23 factorial design. It was verified a significant effect for third order interaction for the intensity of iodine redox peak currents, so the instrumentals parameters were evaluated together. The results of optimization were tpulse = 0.05 s, = 40 mV/s e Epulse = 50 mV. Accordingly, the modified electrode obtained a linear response for iodine concentrations ranging from 4.34 x 10-5 to 3.47 x 10-4 mol L-1 (R=0,9936) and from 4.40 x 10-4 to 4.24 x 10-3 mol L-1 (R=0,9938). It was obtained limit of detection (LOD) 5.56 x 10-6 and 1.51 x 10-5 mol L-1 and for limit of quantification (LOQ) 1.85 x 10-5 and 5.04 x 10-5 mol L-1, respectively. The AgNPs-Am synthesized in this work also acted as colorimetric sensor for iodine, with three regions of linearity. Two analytical curves were obtained for iodine concentration range from 2.40 x 10-7 to 9.50 x 10-7 mol L-1 and from 2.40 x 10-6 mol L-1 to 1.60 x 10-5 mol L-1. It was obtained a LOD of 1.71 x 10-8 and 1.06 x 10-6 mol L-1 and LOQ of 5.69 x 10-8 to 3.55 x 10-6 mol L-1, respectively for each range. Color variations obtained in these concentrations correspond to interaction between iodine and silver, which were monitored by UV-Vis band showed in 410 nm. At concentrations above 5.50 x 10-5 mol L-1 there is the appearance of blue color, absorbance in 600 nm, corresponding to the interaction between starch and iodine. It was also obtained a linear relationship for iodine concentration from 5.50 x 10-5 mol L-1 to 9.50 x 10-5 mol L-1. For this concentration range, LOD and LOQ were respectively 1.37 x 10-6 and 4.58 x 10-6 mol L-1. The results presented confirm the potential use of AgNPs-Am for iodine detection, both for the modification of electrodes for electrochemical determination as a colorimetric sensor.